ETR : E-light Npd / Nurfarahain Mohamad Fauzi ... [et al.] - Mohamad Fauzi, Nurfarahain; Mokhtar, Nurin Nazirah; Kairuddin, Nurul Nadia; Dasan Sandin, Priscillia Durrie; Ibrahim, Siti Nur Aisya (2019)
E-Light is the next generation of highlighter. This innovation is a convenient highlighter that attached with USB flash drive and other additional technology such as on and off button, touchable menu screen and scanner. This device allows to digitally 'highlight' words in any book, and the words are then transcribed onto the computer automatically. The idea of combining these features on a highlighter is due to the current highlighter that has a very limited function that can only 'highlight' words in a book which would require significant more time and work to survive the passage of time. Besides, to make improvements to existing highlighters that cannot be used for a long time because fast running out of ink.